HUBUNGAN KARAKTERISTIK PERAWAT DENGAN TINGKAT STRES PERAWAT DALAM MERAWAT PASIEN DENGAN RESIKO PERILAKU KEKERASAN DI RUMAH SAKIT JIWA TAMPAN PEKANBARU - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2016)
People with mental disorders in the world according to the WHO in 2007, says 1 in 4 people in the world will be affected by a mental disorder at one stage in his life. The nurse is one of the health workers who care for patients with mental health disorders. Nurses soul inclined or at risk of experiencing stress in caring for patients at risk for violent behavior. The purpose of this research is to know is there any relationship Characteristics Nurse Nurse With Stress Levels In Patients With Risk Behavior Caring Violence In Mental Hospital Handsome Pekanbaru 2014. This type of research is quantitative research with descriptive analytic design. The population of all nurses working in the Mental Hospital Pekanbaru Handsome, with a sample of 54 people. The sampling technique is simple random sampling. The data collection is done Primer is to ask directly to the respondent. Analysis of the data univariate and bivariate. Results of univariate research that has been done shows that level of knowledge of the majority is sufficient as many as 30 people (55.6%). The education level of the majority is DIII 31 people (57.4%). The level of stress experienced by respondents is secondary totaling 28 people (51.9%) and bivariate analysis there is a correlation with the stress level of knowledge obtained Pearson chi-square value of 31.821 and 0.000 pvalue with significant tariff of 0.05 and no relationship with the nurse education stress levels, obtained Pearson chi-square value of 14.887 and 0.021 pvalue with significant tariff of 0.05.